The Prioritization of Technical Debt Types in South African Financial Services - Maphosa, Amos (University of the Witwatersrand, Johannesburg, 2019)
Technical Debt hinders software development projects by reducing the speed of IT teams during development cycles. Although technical debt is assessed on either software artifacts or the entire application, the craftsmanship of IT resources causes the accumulation of technical debt. In this paper, I investigate two research questions related to the prioritization of technical debt among the respondents in the South African financial services. The results of 72 recorded respondents were analyzed using a quantitative data analysis approach. The analysis revealed that the Architecture Technical Debt type has the highest level of contribution to Technical Debt with 23.44% of respondents stating so. The analysis further revealed that the System Quality attribute should not be compromised with 17.42% of the respondents attesting to that. Lastly, IT strategy was deemed by 15.04% of the respondents to be the aspect of the IT risk framework to use in prioritizing the Architecture Technical Debt type.
A research report submitted in fulfillment of the requirements for the Master of Business Administration, in the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2019
Keywords: UCTD; Technical Debt; Technical Debt Types; South African Financial Services; SDG-8: Decent work and economic growth